Revisiting the impact of ESG on financial performance of FTSE350 UK firms: Static and dynamic panel data analysis - Nisar Ahmad; Asma Mobarek; Naheed Nawazesh Roni (Cogent Business & Management, 2021)
This study re-examines the impact of ESG (economic, environmental, social, and corporate governance performance) on the financial performance of UK firms. Most recent sample of 351 firms from FTSE350 for the time period 2002-2018 is used. The study estimates the impact of total ESG and individual dimensions of ESG on corporate financial performance using static and dynamic panel data techniques, and it also examines the impact of high and low ESG on firm financial performance. Further, the study investigates the role of firm size as a moderator in the relationship between ESG and firm financial performance. The results of total ESG performance indicate that ESG has a positive and significant impact on firm financial performance. However, in the case of the individual ESG performance, the results are mixed. Overall, the results confirm that high ESG firms show high financial performance as compared to low ESG firms. Results indicate that firm size moderates the relationship between ESG performance and firm financial performance.
Keywords: K32; Q20; 650; Financial performance; Corporate ESG performance; FTSE350 UK firms; Moderator; Static and dynamic panel data analysis; Financial performance; Corporate ESG performance; FTSE350 UK firms; Moderator; Static and dynamic panel data analysis